Exposing image forgery by detecting traces of feather operation. (April 2015) - Zheng, Jiangbin; Zhu, Tingge; Li, Zhe; Xing, Weiwei; Ren, JinChang
Abstract: Powerful digital image editing tools make it very easy to produce a perfect image forgery. The feather operation is necessary when tampering an image by copy–paste operation because it can help the boundary of pasted object to blend smoothly and unobtrusively with its surroundings. We propose a blind technique capable of detecting traces of feather operation to expose image forgeries. We model the feather operation, and the pixels of feather region will present similarity in their gradient phase angle and feather radius. An effectual scheme is designed to estimate each feather region pixel׳s gradient phase angle and feather radius, and the pixel׳s similarity to its neighbor pixels is defined and used to distinguish the feathered pixels from un-feathered pixels. The degree of image credibility is defined, and it is more acceptable to evaluate the reality of one image than just using a decision of YES or NO. Results of experiments on several forgeries demonstrate the effectiveness of the technique. Highlights: A blind technique of detecting traces of feather operation image forgeries. Modeling influence of feather operation by gradient phase angle and radius. An approach to expose image forgeries region by traces of feather operation. The degree of credibility is defined to evaluate the reality of one image.